Análise do melhoramento da estabilidade de frequência do sistema elétrico isolado de Roraima após a introdução de uma nova matriz geradora - Ribeiro, Marcos Fellipe de Souza (2024)
The stability of an electrical system guarantees the quality in which electrical energy will be supplied to the final consumer in an uninterrupted manner. Stability studies and analyzes must be carried out on a steady-state and transient-state basis in order to promote mitigating solutions for existing risks. This paper aims to analyze the stability of the isolated electrical system in Roraima, which since 2019 has started an energy transition process from a diesel-fuel generation matrix to a diversified generator park using biomass and natural gas. Several transient stability studies were carried out to perform comparisons between the current and previous generation facilities. The results obtained have shown that the frequency stability of the isolated electrical system in Roraima, after the energy transition, is now much more stable and reliable.